The availability of the components of the integrated curriculum in the content of primary school mathematics books (Journal of the College of Basic Education, 2025)
The research aims to determine the availability of the components of the integrated curriculum in the content of primary school mathematics books. In order to achieve the research objective, the descriptive analytical approach was used. The research community was determined by the content of the mathematics books prescribed for the lower primary stage. The research sample consisted of the research community itself, after excluding the introductions, titles, and table of contents of the books from the analysis. The research tool was represented by preparing an analysis card that included the components of the integrated curriculum (STEAM). The validity of the analysis was verified, as the content of the books was analyzed according to the components of the integrated curriculum (STEAM), using repetition and percentages. The (Holsti) equation was also used to calculate the stability of the analysis between the researcher and himself over time and between analysts. The research concluded that the availability of the components of the integrated curriculum between science, technology, engineering, arts, and mathematics (STEAM) for all chapters of mathematics books for the first, second, and third grades of primary school was in the following sequence: the mathematics component came in first place with a percentage of (88.22%), with (3676) repetitions, followed by arts with a percentage of (5.76%), with (240) repetitions, then technology with a percentage of (3.19%) with (133) repetitions, then engineering with (1.49%) with (62) repetitions, then science with (1.34%) with (56) repetitions. In light of this, the researchers recommended the need for primary school mathematics curriculum developers to pay attention to the requirements and topics that did not receive sufficient availability within mathematics books and to achieve the integrated curriculum (STEAM) in an appropriate manner, and for the Ministry of Education to prepare and train professional development programs for mathematics teachers to apply the integrated curriculum (STEAM) and to identify the methods of its implementation. The researchers suggested some proposals, including conducting studies to analyze and evaluate the content of mathematics curricula in the general education stages in light of the STEAM methodology.